Factors Affecting Employee Retention in Nepalese Insurance Sector - Basnet, Sailendra Kumar (Dibyajyoti Journal, 2024)
This study investigates the relationship between employee retention and issues within Nepalese insurance companies. The research uses a descriptive and causal-comparative design to explore the challenges of high turnover rates and employee dissatisfaction. The population includes 11,496 employees, with a focus on 385 employees. Data collection involves surveys with selected participants, primarily through closed-ended questions. The findings reveal significant relationships between employee retention and factors such as rewards, workload, career development opportunities, and work culture. Rewards are identified as the most influential factor, with a strong positive impact on retention. Career development opportunities and work culture also play significant roles in retaining employees. Workload has a more modest effect on retention. The study emphasizes the importance of a positive work culture, which can enhance employee morale and reduce turnover.